Career Selection of Professional Accounting: Determination of Internal and External Factors During the New Normal Era in S1 Accounting Graduates in Indonesia - Carlos Pangestu, Juan; Merna Surjadi (Dinasti International Journal of Economics, Finance & Accounting, 2022)
This study examines the accounting graduates (S1) in Indonesia. Specifically, this study examines Determination of Internal and External Factors of Careeer selection of Professional accounting in this study, the research subjects used were Accounting Students at several universities in Indonesia, especially in Java, namely: the city of Jakarta, the city of Bandung, and the city of Surabaya. This study uses quantitative methods by using the type of research conducted with quantitative approaches and data. Based on the results of research and discussions that have been carried out, conclusions can be drawn: Perception of Professional Accountants has a significant influence on the Career Interest of a student in a career as a Public Accountant. The interest of an accounting graduate who will pursue his career as a public accountant starts from the person's perception of the professional public accountant itself. Knowledge of Accounting has no significant and positive effect on Public Accountant Career Interest. As an accounting graduate who will determine his career as a Public Accountant, it is an absolute requirement to have knowledge of Accounting Science, especially in Financial Accounting Standards and International Financial Reporting Standards. This has a significant and positive effect, where with in-depth and adequate Accounting Science, a person will be right in determining his career to become a reliable and professional Public Accountant.